Changes in serum cortisol and blood glucose concentrations in anesthetized, pain-free dogs administered fentanyl. (July 2019) - Romano, Marta; Portela, Diego A.; Verdier, Natali; Otero, Pablo E.
Abstract: Objective: To evaluate whether fentanyl administered at analgesic doses in pain-free anesthetized dogs increases the serum cortisol or blood glucose concentrations and is associated with postanesthetic dysphoria. Study design: Experimental, blinded, randomized crossover. Animals: A group of six adult research dogs. Methods: Each dog was anesthetized twice and was administered fentanyl or saline with a 15-day wash-out period. Treatment allocation was randomly assigned via a closed envelope technique. Cortisol and glucose concentrations were measured on arrival in the research room (TPRE ), induction of general anesthesia (TIND ), extubation (TEXT ) and 1 hour after extubation (TPOST ). Dogs were premedicated with methadone (0.1 mg kg −1 ) and carprofen (4 mg kg −1 ) intravenously (IV), anesthesia induced with propofol (4–6 mg kg −1 ) IV and maintained with isoflurane in oxygen. Standard anesthesia monitoring was performed throughout the experiment. Fentanyl (5 μg kg −1 over 90 seconds followed by 7.5 μg kg −1 hour −1 ) or an equivalent amount in mL of saline solution were administered IV for 60 minutes. TPRE behavior scores and recovery scores were evaluated using descriptive 4-point scales. Data from serum cortisol and blood glucose concentrations were analyzed with a Split Plot on time test, whereas recovery scores were analyzed using a Wilcox match-pairs signed rank test. Statistical significance was set at p < 0.05. Results: There were no significant increases in serum cortisol and blood glucose concentrations over time, and there were no differences between treatments. None of the dogs developed postanesthetic dysphoria with either treatment. Conclusions and clinical relevance: Fentanyl, administered at analgesic doses to healthy, pain-free, anesthetized dogs, was not associated with significant changes in serum cortisol or glucose concentrations in the studied population.